2015
DOI: 10.1134/s0036024415090204
|View full text |Cite
|
Sign up to set email alerts
|

Structure of aldehyde cluster ions in the gas phase, according to data from ion mobility spectrometry and ab initio calculations

Abstract: Ion-mobility spectra of a set of aliphatic linear aldehydes with the number of carbon atoms from 3 to 7 are obtained. Values of the mobility corresponding to two most intense peaks, considered to be those of a monomer and dimer, are determined according the spectra. Based on mobility, collision cross sections are calculated using the Mason-Schamp equation. The linear increase in the collision cross sections upon an increase in molecular weight is determined. According to the experimental results, the contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…High content could promote the combination of protonated molecules and neutral molecules in the ionization region to form dimers . In addition, the formation of dimers was also linked to the high proton affinity of analytes, which was in accordance with the research of Lantsuzskaya et al . In their investigation, it was found that the protons of the reactants were transferred to high proton affinity compounds, and further formed dimer or polymer when the proton affinity of some compounds was higher than that of water.…”
Section: Resultssupporting
confidence: 84%
“…High content could promote the combination of protonated molecules and neutral molecules in the ionization region to form dimers . In addition, the formation of dimers was also linked to the high proton affinity of analytes, which was in accordance with the research of Lantsuzskaya et al . In their investigation, it was found that the protons of the reactants were transferred to high proton affinity compounds, and further formed dimer or polymer when the proton affinity of some compounds was higher than that of water.…”
Section: Resultssupporting
confidence: 84%
“…Due to their different concentrations, it was observed that certain single compounds might produce dimers ( 31 ). The formation of dimers was also associated with its high proton affinity, consistent with the research ( 32 ). As shown in Figure 4 , fingerprinting was used to analyze the differences in the volatile compound content of shrimp meat under different frying methods and temperatures.…”
Section: Resultssupporting
confidence: 90%
“…The reason for this phenomenon was that the monomer and dimer forms of the same compound could exhibit similar retention times coupled with different migration times, correlating with the substance contents [ 31 ]. In the ionization region, a high level of content could accelerate the combination of neutral molecules and protonate molecules to form dimers, and a high proton affinity of analytes could also form dimers [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%